Earthworms regulate ability of biochar to mitigate CO2 and N2O emissions from a tropical soil - Namoi, Nictor; Pelster, David E.; Rosenstock, Todd S.; Mwangi, Lukelysia; Kamau, Solomon; Mutuo, Paul M.; Barrios, Edmundo (Elsevier, 2019)
Soils account for >80% and 20% of the total agricultural N2O and CO2 emissions respectively. Soil management activities that target improved soil health, such as enhancing earthworm activity, may also stimulate further emissions of CO2 and N2O. One recommended strategy for mitigating these soil emissions is biochar amendment. However greater clarity on the interaction between earthworm activity and biochar, and subsequent impact on CO2 and N2O are needed to evaluate the environmental impacts of management practice. We measured N2O and CO2 emissions from a kaolinitic Acrisol in the presence or absence of earthworms, with and without application of two different biochars in a microcosm study. The two biochars were derived from indigenous trees; Zanthoxylum gilletii and Croton megalocarpus, and were tested at three application rates of 5 Mg ha−1, 10 Mg ha−1 and 25 Mg ha−1. Emissions of CO2 and N2O increased by 26% and 72% respectively in the presence of earthworms. In microcosms with biochar and earthworms however, emissions depended on type of biochar and rate of application. With C. megalocarpus, CO2 emission increased with increasing rates of biochar application with 25 Mg ha−1 resulting in higher CO2 fluxes compared to no-biochar control (p = 0.002), while no change was observed with Z. gilletii at the same rate. Nitrous oxide emissions were suppressed at 25 Mg ha−1 for both C. megalocarpus (p = 0.009) and Z. gilletii (p = 0.011). Reduction in N2O flux was however not consistent across biochar types. No change in N2O was observed with 5 Mg ha−1 and 10 Mg ha−1of C. megalocarpus. Biochar from Z. gilletii at 5 Mg ha−1 however led to increase in N2O emissions (p < 0.001). Our findings suggest that earthworms may moderate the effect of biochar, with suppression of N2O emissions occurring at only high biochar application rates, which may occur at the cost of increasing CO2 emissions. These findings contrast with biochar suppressing effect on N2O emissions even at moderate biochar rates of (10 Mg ha−1) when in absence of earthworms, an outcome typical of many laboratory experiments. These findings highlight new interactions among application rate, source of biochar (and hence properties) and earthworms.